2021
DOI: 10.1136/bmjgh-2020-003559
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling respectful maternity care as a way to address global inequities in maternal health

Abstract: To cite: Asefa A. Unveiling respectful maternity care as a way to address global inequities in maternal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…These findings align with a 2015 systematic review by Bohren et al which found that health system factors, such as a lack of privacy or staffing shortages, can be experienced directly by women as mistreatment [ 3 ]. Our study’s findings are consistent with the global literature that suggests mistreatment is not merely an interpersonal problem, but is also driven by health system inadequacies that affect clients and providers alike [ 10 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…These findings align with a 2015 systematic review by Bohren et al which found that health system factors, such as a lack of privacy or staffing shortages, can be experienced directly by women as mistreatment [ 3 ]. Our study’s findings are consistent with the global literature that suggests mistreatment is not merely an interpersonal problem, but is also driven by health system inadequacies that affect clients and providers alike [ 10 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…Asefa et al [43.] , [44.] states it is crucial to work towards strengthening health systems that are capable of promptly responding to shocks and upholding quality of care in times of public health crisis such as the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…It requires structural/institutional commitments, policy backing, and human resource recalibration. Hence, continuous professional development would be to be implemented in order to reduce the occurrence of disrespect [ 35 ]. Our findings also emphasise the need to champion patient-centred care and a rights-based approaches in promoting RMC.…”
Section: Discussionmentioning
confidence: 99%